Understanding Light Art In A Multidisciplinary Context - Coulter, Gerry (European Scientific Journal, ESJ, 2016)
This paper argues that the making of art through the medium of light (Light Art – both artificial and solar), will continue to elevate human existence so long as its makers remain committed to illusion as opposed to the banality of the real. When an art form becomes obsessed with the real it loses sight of the central power of art – the power of making illusion. Light Art thrives in a multidisciplinary world of knowledge where artists understand that the “real” hides behind appearances. Under such a view we may combat singular interpretations in favor of multiple meanings. When we sacrifice a focus on illusion (so essential to art making) for the banality of the “real” world we venture into a kind of anti-art which I term “art-lite” – one of the many manifestations of weak art which proliferates in the art world today. On the side of Light Art as an art of illusion stand many important areas of study today. In this paper I point to several of these (physics, optical science, history, art history, poetics, computer science, mathematics, sociology and social criticism, digital studies, photography, skiagraphy, and aesthetics). This paper argues that Light Art can continue to play an elevating role in our lives due to the very nature of the multidisciplinary perspectives we deploy to challenge, understand, and complete it. The presence of these multiple and intersecting areas of analysis will continue to serve Light Art and place high demands on its makers – including the most important demand that Light Art, like all true art, be concerned with illusion ever avoiding the banalities of the real.